Irma Vidal: a journey through the profession of scenic illuminator (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
Irma Vidal, born in Rio Grande do Norte and living in Bahia since the 1970s, is a lightning artist, Professor at the ICEIA Cultural Center, producer and technical advisor at Teatro Castro Alves, where she has also worked as stage director and technical manager of Balé Theater. She is recognized for her trajectory of more than 40 years on the stage and she guarantees a female technical representation in the backstage of the region. In an interview with A LUZ EM CENA, she shares her paths in stage lighting and talks about her experience behind the scenes around the world. She also gives some advice for the new generation that chooses the professional technical market of cultural making. Winner of many awards for her lighting projects for great artists and directors, she also talks about her systematization research that is being developed in the professional master's degree at the Federal University of Bahia (UFBA) and talks about her wishes as a mentor in the training of new illuminators.
Keywords: scenic lighting; Irma Vidal; northeastern Illuminator; lighting dialogues